2013
DOI: 10.1089/jmf.2012.2534
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Phosphatase and Tensin Homolog by Silymarin to Inhibit Human Pharynx Squamous Cancer

Abstract: Silymarin is an active principle from the seeds of the milk thistle plant and is widely used as a hepatoprotective gent due to its antioxidant-like activity. In the present study, we evaluated the potential efficacy of silymarin against oral cancer and investigated its possible mechanism of action. Cell viability assay and western blotting analyses were used to identify silymarin-induced apoptotic cell death in human pharynx squamous cell carcinoma (FaDu) cells. The short interfering RNA (siRNA) is used to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…PTEN is involved in the regulation of metastasis, apoptosis, proliferation and cell cycle progression, and low PTEN expression has been reported to be associated with the progression and development of human pharyngeal squamous cell cancer ( 27 , 28 ). A previous study reported that PTEN acted as a downstream target gene of miR-9 and functioned as a mediator of miR-9 in laryngocarcinoma cells, which suggested that miR-9 could bind to the PTEN 3′-UTR to inhibit its transcription ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is involved in the regulation of metastasis, apoptosis, proliferation and cell cycle progression, and low PTEN expression has been reported to be associated with the progression and development of human pharyngeal squamous cell cancer ( 27 , 28 ). A previous study reported that PTEN acted as a downstream target gene of miR-9 and functioned as a mediator of miR-9 in laryngocarcinoma cells, which suggested that miR-9 could bind to the PTEN 3′-UTR to inhibit its transcription ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency magnetic fields have been demonstrated to significantly increase the intracellular ROS levels in many kinds of cells [16]. The PI3K/AKT pathway is a pivotal signaling pathway, which is closely related to the regulation of cell survival, apoptosis, migration and proliferation [17]. The relationship between ROS and the PI3K/AKT pathway in apoptosis regulation has been confirmed in several studies [18,19].…”
mentioning
confidence: 82%
“…This can lead to the development of tumors in a variety of cancers [16]. Thus, the induction of PTEN expression by therapeutic agents or natural ingredients is also a strategy for preventing cancers [1,6,21,23]. Several papers have supported the importance of PTEN for cancer prevention by treatment with natural products, including neem leaf and silymarin, which induce expression of proapoptotic genes, including PTEN [1,21].…”
Section: 5)-trisphosphatementioning
confidence: 99%
“…Thus, the induction of PTEN expression by therapeutic agents or natural ingredients is also a strategy for preventing cancers [1,6,21,23]. Several papers have supported the importance of PTEN for cancer prevention by treatment with natural products, including neem leaf and silymarin, which induce expression of proapoptotic genes, including PTEN [1,21]. Interestingly, red wine constituents, including resveratrol, have been reported by many investigators to exhibit inhibitory effects on cancer growth via PTEN expression [2,23].…”
Section: 5)-trisphosphatementioning
confidence: 99%